Educational Evaluation: Classic Works of Ralph W. Tyler
XVII, 310 p.
Keywords: I personally learned to know Ralph Tyler rather late in his career when, in the 1960s, I spent a year as a Fellow at the Center for Advanced Study in the Behavioral Sciences at Stanford. His term of office as Director of the Center was then approaching its end. This would seem to disqualify me thoroughly from preparing a Foreword to this "Classic Works. " Many of his colleagues and, not least, of his students at his dear Alma Mater, the University of Chicago, are certainly better prepared than I to put his role in American education in proper perspective. The reason for inviting me is, I assume, to bring out the influence that Tyler has had on the international educational scene. I am writing this Foreword on a personal note. Ralph Tyler's accomplishments in his roles as a scholar, policy maker, educational leader, and statesman have been amply put on record in this book, not least in the editors' Preface. My reflections are those of an observer from abroad but who, over the last 25 years, has been close enough to overcome the aloofness of the foreigner. Tyler has over many years been criss-crossing the North American con tinent generously giving advice to agencies at the federal, state, and local levels, lecturing, and serving on many committees and task forces that have been instrumental in shaping American education.